FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI SAWI DI DESA MAHARATU KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Shorea Khaswarina; Suardi Tarumun; Etik Purnami (Universitas Sebelas Maret, 2016)
The most people in Indonesia depend of the live at agriculture sector. The vegetables are one of agriculture comodity can to give big contribute to economy if attemted optimally. The efforts of improvement the vegetable production influenced by factors are environment (climate, soil, etc), production facility (seed, fertilizer, pesticide), capital and human resources. The research aim are to analyze influence of production factors to vegetable produce and analyze of allocation efficiency of production factors using to mustard farm. This research was conducted in the Maharatu Village Marpoyan Damai Subdistrict using the purposive sampling method with 40 mustard farmers. The results showed that production of mustard influenced by the seed, manure, urea, NPK, pesticide and labor with belief level 99 %. Score of MPP for all production variable showed that must add volume of production factors to increase mustard production. NPM/px value for seed and urea manure is big than 1 that mean the farmers can be add volume of production factors. For NPK manure, pesticide and labor must not be increasing because value of NPM/px is small than 1 to reach efficient condition economically and get optimally benefit.